Blow-Spun Nanofibrous Membrane for Simultaneous Treatment of Emulsified Oil/Water Mixtures, Dyes, and Bacteria - Lu, Tao; Cao, Wenxuan; Liang, Hebin; Deng, Yankang; Zhang, Yingying; Zhu, Miaomiao; Ma, Wenjing; Xiong, Ranhua; Huang, Chaobo (Langmuir, 2022)
Membrane separation is of great significance due to its unique performance in treating wastewater. However, the simultaneous treatment of oily emulsions and other complex pollutants in water remains challenging. Herein, we have proposed a simple strategy to prepare a multifunctional titanium dioxide/silver nanoparticles/polyacrylonitrile (TiO /AgNPs/PAN) nanofibrous membrane. The experimental results showed that the combination of the hierarchical structure composed of PAN nanofibers and Ag/TiO nanoprotrusions contributed to the superhydrophilicity and superoleophobicity (UOCA = 153.3 ± 2.0°). Further, the nanofibrous membrane exhibited a rapid gravity-driven permeate flux (>1829.37 ± 83.51 L m h ) and an ultrahigh separation efficiency (>99.9%) for the surfactant-stabilized oil/water emulsions. Moreover, due to the synergistic effect between the PAN fibers and TiO /Ag heterojunction, Rhodamine B dye in water can be removed quickly and efficiently (up to 97.67% in 90 min). More importantly, the obtained nanofibrous membrane exhibited ultrahigh stability in different harsh environments. The design of superoleophobic nanofiber membrane with a high separation efficiency and high photocatalytic activity has great potential for practical applications in the purification of oily wastewater.